Evaluate the limit of the function f(x)=(x^2-7x+6)/(x-1) , x-->1 .

2 Answers | Add Yours

tonys538's profile pic

tonys538 | Student, Undergraduate | (Level 1) Valedictorian

Posted on

The limit `lim_(x-> 1)(x^2-7x+6)/(x-1)` has to be determined.

If we substitute x with 1, x^2 - 7x + 6 = 1 - 7 + 6 = 0 and x - 1 = 1 - 1 = 0.

The expression `(x^2-7x+6)/(x-1) = 0/0` which is indeterminate. As a result we can use l'Hospital's rule and replace the numerator and denominator by their derivatives.

`(x^2-7x+6)' = 2x - 7`

`(x-1)' = 1`

The limit is now:

`lim_(x->1) (2x - 7)/1`

Substituting x = 1 gives `(2*1-7)/1 = -5`

The required limit `lim_(x-> 1)(x^2-7x+6)/(x-1) = -5`

giorgiana1976's profile pic

giorgiana1976 | College Teacher | (Level 3) Valedictorian

Posted on

First, we'll verify if the limit exists, for x = 1, so, we'll substitute x by 1 in the expression of the function.

lim f(x) = lim (x^2-7x+6)/(x-1)

lim (x^2-7x+6)/(x-1) =  (1-7+6)/(1-1) = 0/0

We notice that we've get an indetermination case.

We could apply 2 methods for solving the problem.

The first method is to calculate the roots of the numerator. Since x = 1 has cancelled the numerator, then x = 1 is one of it's 2 roots.

We'll use Viete's relations to determine the other root.

x1 + x2 = -(-7)/1

1 + x2 = 7

x2 = 7 - 1

x2 = 6

We'll re-write the numerator as a product of linear factors:

x^2-7x+6 = (x-1)(x-6)

We'll re-write the limit:

lim (x-1)(x-6)/(x - 1)

We'll divide by (x-1):

lim (x-1)(x-6)/(x - 1) = lim (x - 6)

We'll substitute x by 1:

lim (x - 6) = 1-6

lim (x - 6) = -5

The limit of the given function f(x) = (x^2-7x+6)/(x-1) is:

lim (x^2-7x+6)/(x-1) = -5

We’ve answered 318,911 questions. We can answer yours, too.

Ask a question